Comparison of visual reaction values of elite deaf wrestlers and elite normally hearing wrestlers - Tatlici, A.; Çakmakçi, E.; Yilmaz, S.; Arslan, F. (Turkish Journal of Sport and Exercise, 2018)
The research was conducted with the aim of examining the visual reaction values of deaf elite wrestlers (D) and normally hearing elite wrestlers (H). To work, 9 deaf wrestlers (height 179,55±3,74, body weight 78±11,09) and 9 normally hearing wrestlers who participated in national and international competition were voluntarily joined the research. All of the athletes who are deaf subjects consist of at least 55 dB hearing loss in both ears. The visual hand reaction values of the wrestlers were measured using the electronic reaction time meter Newtest 1000. In the study, all participants` dominant hand were right hand. The data were analyzed using the SPSS (Version 22.0) program. Independent T test was performed to determine the difference between the two groups in which the obtained data showed normal distribution. The significance level was evaluated as p <0.05. In the study findings, the average of right and left hand reaction timing between groups and between intergroup were similar, D group had significantly higher height and body weight averages than group N (P <0.05). As a result; deaf athletes have similar reaction times to normal athletes so it is seen that loss of hearing does not make a difference at least in the result of this study.